UMP Eco Ride to promote the cycling sport - Norhidayah, Mohamad (2017)
The 1st International UMP Eco Ride 2017 was a success with more than 500 participations from cycling fans. As well as promoting cycling, this activity also promotes Visit Pahang Year 2017 where the route they were taken shows the beauty of Pahang.